Análise das tensões atuantes em interseções entre bocais e vasos de pressão cilíndricos sem e com chapa de reforço sob pressão interna - Jorge Ricardo Fonseca de Miranda (2007)
In this work the stress fields on vessel/nozzle intersections of cylindrical pressure vessels were evaluated using finite element models. ANSYS Workbench finite element tool was used as platform to develop three-dimensional models with 20-node solid elements. Three models were developed, concerning the vessel/nozzle intersection: (i) unreinforced vessel/nozzle intersection; (ii) bonded pad reinforced vessel/nozzle intersection (pad is integrally welded on the vessel/nozzleintersection); and (iii) partially welded pad reinforced vessel/nozzle intersection (borders of the pad are considered bonded simulating welding lines and friction contact hypothesis is assumed in the pad/vessel contact surface). Reinforcement pads were designed according to ASME Code Criteria Area Replacing Method. Linear (models i and ii) and nonlinear (model iii) elastic analysis were performed. Results obtained correlated well with experimental results obtained from the literature for model i. The influence of the reinforced pad is demonstrated. Comparisons between models ii and iii showed considerable differences on the stresses levels. While the tangential stresses reached values up to 10% higher than those levels of model ii, the radial ones augmented from 2,5 MPa to 19,2 MPa for model iii. This suggests that a more accurate representation of the real structure should be considered